ENTREPRENEURSHIP AND INDEPENDENCE IN ISLAMIC BOARDING SCHOOL (STUDY OF ENTREPRENEURSHIP MANAGEMENT AT MBS PRAMBANAN) - AM Saifullah Aldeia; Israpil Israpil (Balai Penelitian dan Pengembangan Agama Makassar, 2021)
The implementation of entrepreneurial activities is an important element that must receive attention by Islamic boarding school managers so that they can become independent educational institutions. Its implementation must also be carried out systematically through the implementation of management functions. The problem of this study is as to why entrepreneurship needs to be developed in the Muhammadiyah Boarding School (MBS) ; how is the practice of entrepreneurial management in building independence in the MBS. This study aims to describe the entrepreneurial management process as an effort to build independence in the MBS. This research method is qualitative method using a phenomenological approach. The results of this study show that: (1) since its inception in 2008, the MBS has made the entrepreneurship program part of the master plan for institutional development. (2) In the management of entrepreneurial activities, management functions are applied, namely from planning, organizing, implementing and supervising. (3) The planning function is implemented in work meeting activities held at the beginning of each academic year. (4) Organizing function is implemented through the transfer of authority from the director of the Islamic boarding school to the manager of the waqf center institution. (5) The implementation function in entrepreneurial activities at the MBS is described in three core activities, namely coordinating, delegating, and commanding. (6) the supervisory function is carried out incidentally by the Wkaf center manager and routinely by the head of the unit by evaluating individual work assessment report cards. (7) The existence of a business unit is capable of supporting the Islamic boarding school's economy and finances. In addition, Islamic boarding school is also capable of being independent as it can provide the required resources through their business units.